2009
DOI: 10.1007/s11738-009-0330-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of Psoralea corylifolia L. by somatic embryogenesis in cell suspension culture

Abstract: An effective protocol was developed for in vitro propagation of Psoralea corylifolia via somatic embryogenesis in cell suspension culture. Embryogenic callus was obtained on Murashige and Skoog (MS) medium supplemented with 6 lM naphthaleneacetic acid (NAA) and 30 lM glutamine from transverse TCLs from 10-day-old hypocotyl explants with a 96.4% frequency. Embryogenic callus produced a higher number of somatic embryos (123.7 ± 1.24 per gram fresh weight callus) on MS medium containing 30 g l -1 sucrose, 1 lM NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…1). Similarly, several reports confirmed that formation of SEs was enhanced by glutamine (Baskaran and Jayabalan 2009;Deo et al 2010;Gerdakaneh et al 2011). The role of picloram, TDZ and glutamine on SEs production has also been reported in other plant species (Tribulato et al 1997;Van Staden 2012, 2014).…”
Section: Resultssupporting
confidence: 54%
“…1). Similarly, several reports confirmed that formation of SEs was enhanced by glutamine (Baskaran and Jayabalan 2009;Deo et al 2010;Gerdakaneh et al 2011). The role of picloram, TDZ and glutamine on SEs production has also been reported in other plant species (Tribulato et al 1997;Van Staden 2012, 2014).…”
Section: Resultssupporting
confidence: 54%
“…(Plantain) Maturation of somatic embryos Sholi et al (2009) Nicotiana tabacum Improvement of ex vitro transfer of plantlets by addition to last subculture Pospísilova et al (2009) Phoenix dactylifera (date palm) Accumulation of storage proteins in somatic embryos Sghaier et al (2009) Phragmites communis (reed) Exogenous application of ABA alleviated the heat stress symptoms in the calluses of two ecotypes Ding et al (2010) Picea abies (Norway spruce) Maturation of somatic embryos and expression of the gene encoding transcription Promotion of proliferation of PLBs Liu et al (2010) Pinus brutia (Turkish red pine) Maturation of somatic embryos Yildirim et al (2006) Pinus sylvestris (Scots pine) Maturation of somatic embryos and accumulation of storage proteins Lelu-Walter et al(2008)Pinus taeda (loblolly pine) Improved somatic embryo maturation by monitoring ABA-responsive gene expressionVales et al (2007) Psidium guajava (guava) Induction of quiescent state in encapsulated somatic embryos and maturation of somatic embryosRai et al (2008a) Psoralea corylifolia Embryogenic callus induction and subsequently development and germination of somatic embryosBaskaran and Jayabalan (2009) Quercus suber (Oak) Somatic embryo maturation Garcia-Martin et al…”
mentioning
confidence: 99%
“…68 Bu bitki, psöralen bakımından zengin bir doğal kaynak olarak gösterilmektedir. 69 Cildi, ultraviyole ve güneş ışınlarına duyarlı hâle getiren fotosensibilizan, koruyucu, antistres, antioksidatif özeliklerinden dolayı, geleneksel olarak oral ya da topikal preparatları hâlinde vitiligo tedavisinde uzun zamandan beri kullanılmakta-dır.…”
Section: Pastinaca Sativa L (Apiaceae) Yabani Havuçunclassified